Fostering Learners’ Reading Comprehension Through Adopting Preview, Question, Read, Summarize, And Test (Pqrst) Strategy - Ferdiyanto, Feri; Kholili, Achmad; Fauzi, Ahmad (LP3M UNZAH GENGGONG, 2020)
ABSTRACT As part of English proficiency, reading plays a pivotal role in every aspect of life. Given the fact that reading English is still a big deal for most learners, they often avoid practicing such skill. As a consequence, EFL learners, for the most part, keep suffering from the complexities in reading. Besides, the teaching in Indonesia is mostly teacher centered approach in that it makes them passive. This present paper expounds on PQRST strategy in reading. This paper attempts to eliminate the reading disabilities. PQRST which stands for Preview, Question, Read, Summarize, and Test is strongly recommended to be employed by the students in copying with difficulties in reading. This strategy has the power of succeeding in reading the text since complete steps are sufficiently provided. Hence, comprehension in reading the text will be improved with this strategy. Keyword: English Proficiency, Reading, PQRST